Establishing the Relationship between Financial Hardship and Remittance Inflow in Nepal (Economic Journal of Nepal, 2021)
The objective of the paper is to examine how altruism motives influence the inflows of worker remittances in Nepal.  Evidence suggests that flows of remittances to Nepal had increased significantly in response to the earthquake in April-May, 2015. Remittances to Nepal rose dramatically in response to the earthquake by 20.9 percent in 2015 versus 3.2 percent in 2014. There is also a correlation between the level of remittance and hardship. The paper uses inflation as an indicator of ‘Financial Hardship’ to analyse the role of altruistic motives as a determinant of inflow of remittances. When prices of goods and services increase in the home country, the workers send more money to support their families. The Engel-Granger cointegration test is used to assess the short-run and the long-run relationship between inflation and remittances. Inflation does not affect remittances in the short run, however, there is the long-run relationship between remittances and inflation. It is confirmed that financial hardship determines the remittance inflow in Nepal.